Determinant Parents Of Student’s Decision In Choosing Junior High School (SMP) Education Services In Banten Province And Its Implications On Student Parent Satisfaction - Arianto, Nurmin; Limakrisna, Nandan; Horas V. Purba, Jan (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this study was to determine and analyze the effect of service quality on decisions, costs on decisions, CRM on decisions on satisfaction, service quality on satisfaction, costs on satisfaction, CRM on satisfaction, service quality on satisfaction through decisions and costs on satisfaction through decisions. and knowing CRM to satisfaction through decisions. The population of this research is parents of students who send their children to private junior high schools in Banten Province with a total of 4,707 schools and a sample of 200 schools while the number of parents of students is 370. The research method used in this study is a quantitative method with explanatory survey approach and data analysis methods using SEM with the help of SmartPLS. Based on the results of the study, the following findings were obtained: service quality has a positive and significant effect on decisions, costs have a positive and significant effect on decisions, CRM has a positive and significant effect on decisions, decisions affect satisfaction and service quality has a positive and significant effect on satisfaction, cost has a positive and significant effect on satisfaction and CRM has a positive and significant effect on satisfaction, service quality, cost, CRM has a positive effect on satisfaction through decisions. Therefore, the decision variable is a full mediating variable.The implication of the results of this study is that to increase Parental Satisfaction of Students at Junior High Schools in Banten Province, especially in the high level of Always Buying, it will be able to be increased if Junior High Schools in Banten Province are able to improve Parental Decisions in Choosing Schools, especially on the high dimensions of product choice (choice of choice). product), where the Decision of Parents of Students in Choosing Junior High Schools in Banten Province will be able to be improved if Junior High Schools in Banten Province are able to improve Customer Relationship Management, especially in the high development and increase in Education Costs, especially in the high cost of school supplies and equipment and improve the quality of service, especially in the high level of assurance (guarantee).